Adam Smith and Dynamic Systems - Acuña, Osvaldo (2008)
We present a simple dynamical system with two differential equations, one for price, and another for a good in an economy. Our model is based en the price theory ex-posed by Adam Smith in Wealth of Nations.We studied as an example, the case of cattle for world economy.